Brain Death without Definitions - Chiong, Winston (The Hastings Center report, 2005)
Most of the world now accepts the idea, first proposed four decades ago, that death means “brain death.” But the idea has always been open to criticism because it doesn't square with all of our intuitions about death. In fact, none of the possible definitions of death quite works. Death, perhaps surprisingly, eludes definition, and “brain death” can be accepted only as a refinement of what is in fact a fuzzy concept.